2021
DOI: 10.7717/peerj.11604
|View full text |Cite
|
Sign up to set email alerts
|

Embryo and larval biology of the deep-sea octocoral Dentomuricea aff. meteor under different temperature regimes

Abstract: Deep-sea octocorals are common habitat-formers in deep-sea ecosystems, however, our knowledge on their early life history stages is extremely limited. The present study focuses on the early life history of the species Dentomuricea aff. meteor, a common deep-sea octocoral in the Azores. The objective was to describe the embryo and larval biology of the target species under two temperature regimes, corresponding to the minimum and maximum temperatures in its natural environment during the spawning season. At tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 97 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…Little is known about the larval biology of deep-sea benthic species such as octocorals. Knowledge is limited to some brooding species, with very short PLD (Sun et al, 2010) while others are broadcast-spawners that have different larval characteristics and dispersal capabilities (Rakka et al, 2021). Some authors showed that for sponges a short PLD is an advantage (surviving better, growing faster and with a more regular shape), confirming the hypothesis that long-lived larvae bring fewer reserves to the post-settlement period (Maldonado and Young, 1999).…”
Section: Connectivity Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the larval biology of deep-sea benthic species such as octocorals. Knowledge is limited to some brooding species, with very short PLD (Sun et al, 2010) while others are broadcast-spawners that have different larval characteristics and dispersal capabilities (Rakka et al, 2021). Some authors showed that for sponges a short PLD is an advantage (surviving better, growing faster and with a more regular shape), confirming the hypothesis that long-lived larvae bring fewer reserves to the post-settlement period (Maldonado and Young, 1999).…”
Section: Connectivity Processesmentioning
confidence: 99%
“…Such flows may enhance food supply and provide favourable conditions for the settlement of suspension-feeding fauna, such as cold-water corals and sponges (Mortensen et al, 2008). Larval rearing experiments showed that without aeration, larvae of octocorals have a strong negative buoyancy, remaining at the bottom (Rakka et al, 2021), showing the importance of seabed currents for larval dispersal.…”
Section: Connectivity Processesmentioning
confidence: 99%
“…Larvae of the deep‐sea octocoral Dentomuricea aff. Meteor exposed to high temperature (+2°C) had similar survival as larvae at ambient temperature (Rakka et al, 2021 ). Larvae from two tropical and one temperate octocoral species showed tolerance to temperature conditions expected by 2100 (+3°C; Conaco & Cabaitan, 2020 ; Da‐Anoy et al, 2020 ; Kipson et al, 2012 ; Liberman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies have focused on hexacoral tropical species, whereas octocoral species have been largely neglected. Although octocoral species are present across large depth ranges and in all oceans worldwide, the effects of thermal stress on their early life‐history stages have been studied in only two tropical, one temperate, and one deep‐sea species (Conaco & Cabaitan, 2020 ; Da‐Anoy et al, 2020 ; Kipson et al, 2012 ; Liberman et al, 2021 ; Rakka et al, 2021 ). These studies suggest that octocoral larvae have tolerance to thermal stress.…”
Section: Introductionmentioning
confidence: 99%